Swearwords, Feelings and Emotions - Mulatsih, Devi (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2013)
This article analyzes theuse of swearwords with reference to Sociolinguistic, and Psycological conceptual frameworks. It starts with an emotions and feelings when one is expected to be carful in selecting the words to express his/her thoughts. In the guise of tackling the problem, Sociolinguistic and Psycological explanation is pursued, which in the end, shows that Sociolinguistic explanation is not really adequate to handle the issue. This relates to the possible notion that swearwords might be enacted as a (very) personal expression, devoid of any physical addressees.